Yale companion to Jewish writing and thought in German culture, 1096-1996 - Gilman, Sander L.; Zipes, Jack, 1937- (Yale University Press, 1997)
This book is the first to provide a history of Jewish writing and thought in the German-speaking world. Written by 119 of the most distinguished scholars in the field, the book is arranged chronologically, moving from the eleventh century to the present. Throughout, it depicts the unique contribution that Jewish writers have made to German culture and at the same time explores what it means to be the "other" within that mainstream culture. The contributors view German-Jewish literature as a historical and cultural phenomenon, from a wide array of critical perspectives. Many essays focus on significant social and political events that affected the relationship between Germans and Jews; others concentrate on a particular genre, author, group of writers, cultural debate, or literary movement. Entries include an account of the crusades in 1096, a treatment of Jewish mysticism in the Renaissance, a unique seventeenth-century memoir by a woman, the description of a meeting between Heinrich Heine and Karl Marx in 1843 and discussions of works by such twentieth-century luminaries as Sigmund Freud, Arthur Schnitzler, Joseph Roth, Martin Buber, Walter Benjamin, Elias Canetti, Hermann Broch, Hannah Arendt, Theodor Adorno, and Peter Weiss. By analyzing how individuals and groups defined and expressed themselves as Jewish against the background of a dominant German culture, the contributors bring out the vital currents and crucial moments in two interlocking yet contradictory cultural histories in Germany.